PENGARUH SWITCHING COST DAN SWITCHING INTENTION TERHADAP WOM PADA NASABAH BCA DI KOTA DENPASAR - Wikrami, I A Widya Pryanka; Mandala, Kastawan (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
This study aims to determine effect of switching cost to switching intention and word of mouth as well as the role of switching intention in mediating effects of switching cost to the customer word of mouth at Bank Central Asia in Denpasar. This research was conducted in Denpasar with a population used is the customer who has the BCA stages as well as the sample size of 110 people. The data was collected by distributing questionnaires and Likert scale to measure 11 indicators of the three variables of the study. The analysis technique used in this research is path analysis and test Sobel. The results of this study show that switching cost significant negative effect on switching intention, switching intention significant negative effect on word of mouth, and switching cost significant positive effect on word of mouth. Switching intention can partially mediate effect of switching cost on word of mouth.
Keywords: switching cost, switching intention, word of mouth